E-Government di Asia Tenggara: Perbandingan Pengembangan E-Government di Singapura, Malaysia dan Indonesia - Verdico Arief (Social Issues Quarterly, 2023)
In this paper, the researcher aims to compare the conditions of e-government development in Singapore, Malaysia, and Indonesia. These countries were chosen as samples because the geographical locations of the three countries are very close, and they have many similarities in terms of community life and culture. In fact, the growth of e-government development in these countries is very different. Therefore, the researcher is interested in scrutinizing this phenomenon. In this study, the researcher analyzes the primary documents of the e-government development planning of each country. All documents employed as the data of this research have been recognized as valid by the United Nations. Based on the study results, it was found that the goals and experiences of a country’s e-government development can affect the success of e-government implementation. This article is expected to provide reference and evaluation material for all parties interested in the field of public administration, especially related to e-government.